The Intellectual Legacy of Sharh al-Sunnah: Imam al-Baghawi’s Systematic Defense of the Signs of Prophethood - Parveen, Sidra; Jan, Hafiz Falak Sher (Al-Irfan, 2025)
Imam Al-Baghawi’s Sharh al-Sunnah is a foundational text in Hadith studies and Islamic jurisprudence encompassing theological discourse legal principles and an extensive discussion on the signs of Prophethood (علاماتِ نبوت). This study critically examines the historical significance of the text its methodological framework and Imam Al-Baghawi’s contributions to the preservation and interpretation of the Sunnah. As a distinguished scholar of the Shafi’i school Al-Baghawi adhered to a rigorous and balanced approach in Hadith compilation, classification and legal analysis. A central aspect of Sharh al-Sunnah is its detailed exposition on the signs of Prophethood documenting various miraculous occurrences in the life of Prophet Muhammad (SAWW) including the splitting of the moon, water emerging from his fingers and inanimate objects acknowledging his Prophethood. These narrations serve as theological affirmations of his divine mission. The study further explores Sharh al-Sunnah’s reliance on authentic sources systematic organization and scholarly commentary underscoring its enduring relevance in Hadith scholarship and Islamic law. Given the advancements in manuscript studies, digital tools and Hadith authentication methodologies a contemporary critical analysis of this work is warranted. The findings emphasize Sharh al-Sunnah’s continued significance as an essential reference in classical and modern Islamic scholarship.